2016
DOI: 10.1021/acs.chemmater.6b01729
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired Polydopamine (PDA) Chemistry Meets Ordered Mesoporous Carbons (OMCs): A Benign Surface Modification Strategy for Versatile Functionalization

Abstract: Mussel-inspired polydopamine (PDA) chemistry was employed for the surface modification of ordered mesoporous carbons (OMCs), improving the hydrophilicity, binding ability toward uranium ions, as well as enriching chemical reactivity for diverse postfunctionalization by either surface grafting or surface-initiated polymerization. Uniform PDA coating was deposited on the surface of CMK-3 type OMCs via self-polymerization of dopamine under mild conditions. Surface properties and morphology of the PDA-coated CMK-3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(49 citation statements)
references
References 90 publications
2
45
0
2
Order By: Relevance
“…Many researchers found that membrane surface modification using polymers with adsorption function could improve the removal abilities of membranes for micropollutants . Inspired by the strong adhesion of mussel proteins, dopamine coating technology provided a versatile platform for construction of varied functional membranes . The combination of adsorption and separation process could impart a wider application prospect to these modified membranes …”
Section: Introductionmentioning
confidence: 99%
“…Many researchers found that membrane surface modification using polymers with adsorption function could improve the removal abilities of membranes for micropollutants . Inspired by the strong adhesion of mussel proteins, dopamine coating technology provided a versatile platform for construction of varied functional membranes . The combination of adsorption and separation process could impart a wider application prospect to these modified membranes …”
Section: Introductionmentioning
confidence: 99%
“…Thus, the initiator molecules could be anchored on the surface the materials due to the high concentration of catechol and amine groups on PDA. In addition, it has been recently founded that dopamine could also be used as a reducing agent for GO . In comparison to other reduced procedures, PDA coating is a more green protocol.…”
Section: Introductionmentioning
confidence: 99%
“…Figure S10A (Supporting Information) shows the adsorption and polymerization process for grafting PDA on MoS 2 nanosheets. Seen from their UV–vis absorption spectra (Figure S10B, Supporting Information), PDA layer can be formed on MoS 2 nanosheets in Tris solution (pH 8.5) after being mixed for 40 min . And, the presence of PDA cannot damage the crystalline structure of MoS 2 nanosheets (Figure S10C,D, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%